NEWTON’S LAW OF COOLING -LAPLACE TRANSFORM - NARESH, P. (Journal of Global Research in Mathematical Archives(JGRMA), 2017)
In this paper, I solved the problems occurred in first order ordinary linear differential equations based on Newton’s Law of cooling by using Laplace Transform. Keywords: Laplace transform, Newton’s Law of Cooling, Differential Equations